Ranking 67 Florida Reefs for Survival of Acropora cervicornis Outplants - Banister, Raymond B.; van Woesik, Robert (Frontiers in Marine Science, 2021)
Over the past three decades, coral populations have declined across the tropical and subtropical oceans because of thermal stress, coral diseases, and pollution. Restoration programs are currently attempting to re-establish depauperate coral populations along the Florida reef tract. We took an integrated Bayesian approach to determine which Florida reefs ranked highest based on the survival of outplanted colonies of Acropora cervicornis from 2012 to 2018. Survival of A. cervicornis outplants was highly variable in the upper Florida Keys with some reefs showing the highest likelihood of survival (e.g., North Dry Rocks, Carysfort, Key Largo Dry Rocks, and Conch Reef), whereas some adjacent reefs showed the lowest likelihood of survival (e.g., an Unnamed Reef, Pickles Reef, and U47 Patch Reef). Similarly, survival was highly variable in the middle and lower Florida Keys and in the Broward-Miami subregions. Survival was high and less variable in Biscayne Bay and low and less variable in the Marquesas subregions. The reefs that ranked lowest for outplant survival were exposed to high wave energy. Partitioning out the spatial effects of reefs and subregions from the model, we detected spatial latent effects of low survival that were most evident in the middle and the upper Florida Keys, particularly between 2015 and 2017. The overall high spatial and temporal variability in survival among adjacent reefs highlights a need to outplant nursery-reared colonies strategically, in order to optimize coral-population recovery efforts in Florida.